CONCENTRATION OF SUPPLY ON THE CHOSEN MARKETS OF SERBIAN ELECTRONIC COMMUNICATIONS SECTOR - Kostić, Milan; Živković, Jelena (The European Journal of Applied Economics, 2021)
The electronic communications sector is very important sector of a national economy. It provides an opportunity for facilitating business activities and it is a good area for investment. A small number of operators and a large number of users operate in most markets of the electronic communications sector. The conditions under which electronic communications services are available to users in different countries diverge, among other things, due to the degree of liberalization of individual markets in these countries. The Republic of Serbia has significantly liberalized this sector of economic activity by adjusting it according to the regulations of the European Union. However, certain entry barriers have remained, primarily related to the licenses that operators need to obtain to operate on the Serbian market. The paper aims to investigate the level of concentration in selected markets of the electronic communications sector, namely: mobile telecommunication networks and services, broadband Internet services and media content distribution. The research showed a high level of concentration measured by the Herfindahl-Hirschman index in all three markets. A further increase in concentration is expected in all analyzed markets in the short term. These research results require more attention from regulatory bodies because they increase the possibility of some form of non-competitive behaviour by undertakings.
Keywords: electronic communications sector; market concentration; distortion of competition; competition policy